Impact of Blocking Diodes on Fault Current Behaviour in Photovoltaic Arrays under Line-Ground and Line- Line Faults - Aye Aye Mon; Han Phyo Wai (The Indonesian Journal of Computer Science, 2025)
The maximum power output from a photovoltaic (PV) array is reduced by abnormal situations like faults and partial shading. In order to improve reliability, efficiency and safety in PV systems, fault analysis in solar photovoltaic (PV) arrays is crucial. Blocking diodes play a crucial role in photovoltaic (PV) arrays by preventing reverse current flow and improving system reliability under fault conditions. This paper investigates the impact of blocking diodes on fault current behavior in PV arrays subjected to Line-to-Ground (L-G) and Line-to-Line (L-L) faults. A comparative analysis is conducted between PV arrays with and without blocking diodes to evaluate their effect on fault current magnitude, and power loss. Results indicate that blocking diodes significantly limit reverse fault currents, thereby reducing system damage and enhancing fault isolation.The presence of blocking diodes modifies the I-V characteristics of the PV array, influencing fault detection methodologies. The performance results of 25 kW PV array system are revealed by using a Matlab/Simulink model of 10×5 size of solar array.